Demografski razvoj Koroške med letoma 1948 in 1996 - Krajnc, Dimitrij (Geografski vestnik, 2000)
Presented is the development of Carinthia population for the period 1948 to 1996. We described the demographic development of Carinthia and its communes. We also compared the demographic development in Carinthia with demographic development in Slovenia. The main stress in research was on number of population, fertility, mortality, natural increase and age structure of population.
Keywords: demogeografija; demografski razvoj; demografska struktura; Slovenia; Slovenija; Koroška